Disposal of medical waste: a legal perspective in Zimbabwe - Nyakatswau, Stuart T.; Bangure, Donewell; Pierre, Gashema; Nyika, Howard (International Journal Of Community Medicine And Public Health, 2022)
The constitution of Zimbabwe provides that everyone has the right to an environment that is not harmful to their health and well-being. However, the illegal dumping and inappropriate disposal of hazardous waste poses a danger to the health of scavengers who are directly exposed to it and to the environment when pollutants migrate into water sources, spread into air and ultimately causing widespread of infection and toxicity.2 The safe disposal of hazardous waste is governed by legislation and regulations which in turn gives effect to the constitution.